Pengaruh Konsentrasi Bubuk Wortel (Daucus carota L.) Terhadap Sifat Fisik, Kimia dan Sensoris Mochi - Maharantata, Fayza Desti; Kencana Putra, I Nengah; Diah Puspawati, Gusti Ayu Kadek (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2025)
Abstract Mochi may be a conventional Japanese nourishment made from glutinous rice flour which is prevalent since of its chewy surface, the dietary substance contained in mochi is 75-90% carbohydrates so that it is wealthy in carbohydrates and moo in Β-carotene, and colors that use synthetic colors. One of the endeavors to extend the wholesome substance of Β-carotene in mochi and give common coloring is by including carrot powder which is wealthy in fiber and Β-carotene. This consider points to decide the impact of carrot powder concentration on the physical, chemical, and tangible properties of mochi and to discover out the proper concentration of carrot powder to create mochi with the most excellent characteristics. The think about utilized a Totally Randomized Plan (CRD) with a carrot powder concentration treatment comprising of 6 treatment levels: 0%, 2%, 4%, 6%, 8%, and 10% with three rehashes. Information were analyzed utilizing Examination of Fluctuation (ANOVA) when there was a critical impact (P<0.05), taken after by the Dunces Numerous Extend Test when critical impacts were found. The comes about appeared that the concentration of carrot powder had a genuine impact (P<0.05) on dampness substance, fiery remains substance, unrefined fiber substance, Β-carotene substance, color, hardness, and sensory within the shape of hedonic tests on color, taste, smell, and in general acknowledgment as well as scoring tests on color and taste. The most excellent characteristics of mochi are found within the expansion of 10% carrot powder with a dampness substance characteristic of 40.56%, Β-carotene contents of 4418.93 Î¼g/100 g, ash contents of 2.65%, rough fiber contents of 6.70%, hardness of 0.64 N, color (L* 52.44, a* 23.67, b* 60.56) with a bronze-orange color, as well as the acknowledgment rate of panelists within the category of enjoying with a really orange color and an awfully carroty taste. In this way, the 10% concentration of carrot powder within the mochi detailing can increment the wholesome substance, particularly fiber and Β-carotene, without corrupting its tangible qualities. Keywords: Carrot powder, mochi, β-carotene Abstrak Mochi yaitu makanan tradisional khas Jepang pada bahan dasar tepung ketan yang digemari karena teksturnya yang kenyal, kandungan gizi yang ada di mochi sekitar 75-90% karbohidrat hingga kaya karbohidrat dan rendah kandungan β-karoten, serta warna yang menggunakan pewarna sintesis. Suatu upaya untuk memberi peningkatan pada kandungan gizi β-karoten pada mochi dan mamberi pewarna alami yaitu pada penambahan bubuk wortel yang kaya serat dan β-karoten. Penelitian ini mempunyai tujuannya sebagai mengetahui pengaruh konsentrasi bubuk wortel terhadap sifat fisik, kimia, dan sensoris mochi dan untuk mengetahui konsentrasi bubuk wortel yang sesuai agar menghasilkan mochi pada karakteristik terbaik. Penelitian memakai rancangan Acak Lengkap (RAL) di suatu perlakuan konsentrasi bubuk wortel yang diantaranya 6 taraf perlakuan : 0%, 2%, 4%, 6%, 8%, dan 10% pada tiga kali ulangan. Data dianalisiskan menggunakan sidik ragam apabila ada pengaruh nyata (P<0,05), dilanjutin pada uji jarak berganda Duncan. Hasil penelitian memberi petunjuk jika konsentrasi bubuk wortel mempunyai pengaruh nyata (P<0,05) pada kadar air, kadar abu, kadar serat kasar, kadar β-karoten, warna, hardnes (kekerasan), serta sensoris berupa uji hedonik pada warnanya, rasa, aroma, dan penerimaan semua serta uji skoring pada warnanya dan rasa. Karakteristik mochi terbaik ada di penambahan bubuk wortel 10% pada karakteristik kadar air 40,56%, kadar β-karoten 4418,93 µg/100 g, kadar abu 2,65%, kadar serat kasar 6,70%, hardness 0,64 N, warna (L* 52,44, a* 23,67, b* 60,56) dengan warna oranye bronze, serta tingkat penerimaan panelis pada kategori suka dengan warna sangat oranye dan rasa sangat terasa wortel. Dengan demikian, konsentrasi bubuk wortel 10% pada formulasi mochi bisa memberi peningkatan pada kandungan gizi, khususnya serat dan β-karoten, tanpa menurunkan kualitas sensorisnya. Kata Kunci: Bubuk wortel, mochi, β-karoten